ETHNOMATHEMATICS IN THE RADAP RAHAYU DANCE AND ITS IMPLEMENTATION IN MATHEMATICS LEARNING - Muhamad Sabirin; Muh. Fajaruddin Atsnan; Siti Hilaliyah (EDU-MAT: Jurnal Pendidikan Matematika, 2024)
Radap Rahayu dance is an original dance from South Kalimantan, Indonesia. This dance is a cultural heritage of Banjar, South Kalimantan. It has ethnomathematics potential that needs to be studied. The study aimed to explore the ethnomathematics aspects of the Radap Rahayu dance. The subjects of this research were Banjarmasin cultural figures and artists, dance lecturers and dance teachers The four focuses of this ethnographic research are, finding the mathematical concepts in the movement, musical instrument accompaniment, clothing, and ethnomathematics implementation of the Radap Rahayu Dance in mathematics learning. Data collection techniques using Focus Group Discussion with observation, interviews, and elaboration of the three research subjects. The data analysis technique refers to Miles and Huberman, with data validity using source triangulation. The research results show four things. First, there is a concept of counting, measurement, reflection, circles, and triangles in the Radap Rahayu dance movements/varieties. Second, there is a concept of symmetry, a circle, and an integral symbol on the musical instrument accompanying the Radap Rahayu Dance. Third, there is a concept of a triangle, symmetry, parallel lines, a circle, and dilatation in the costume of Radap Rahayu Dance. And, the implementation of the ethnomathematics aspects of the Radap Rahayu Dance in Mathematics Learning is found in the student module and Worksheets, which contain project-based activities making mathematics more meaningful and fun. Keywords: Ethnomathematics, Radap Rahayu Dance, Mathematics Learning